Pengaruh Sektor Pertanian, Kehutanan, dan Perikanan terhadap Perekonomian Kabupaten Banggai: The Influence of the Agricultural, Forestry and Fisheries Sectors on the Economy of Banggai Regency - Yofandi Djibran Himran; Amir Buhang (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2023)
The purpose of carrying out this research is (1) to find out how the influence the agricultural, forestry and fisheries sectors on the economy between 2011 and 2021 which provides information and analysis results that, based on testing the simple regression coefficient shown by the results of the study, the equation Y = -2,873 + 11,812 X shows that there is an influence between Banggai Regency revenue in agriculture, forestry and fisheries sectors to the economy. The value of the variable (X) is 11,812, meaning that if the agricultural, forestry and fisheries sectors experience an increase of one billion rupiah, then the economy will experience an increase of 11,812 billion rupiah and vice versa. The growth in the contribution of the agriculture, forestry and fisheries sectors has decreased from year to year. This indicates that along with technological developments and education levels, people are starting to look for new ideas and ways not to always depend on nature, so that they are starting to switch to non-agricultural business fields, this will lead to a change in the economic structure from agrarian to modern which puts more emphasis on world of business and industry.